Characterization of Xanthomonas species causing bacterial leaf spot disease of pepper (Capsicum annuum) in India - RAMYASHREEDEVI, G S; SINGH, DINESH; SRIVASTAVA, ARPITA; BISWAS, K K; GUPTA, A K (The Indian Journal of Agricultural Sciences, 2017)
The present study was under taken to characterize and identify prominent species of Xanthomonas causing bacterial leaf spot disease on pepper and their genetic diversity in India. Thirty one isolates of Xanthomonads isolated from infected leaf and fruit samples of tomato, chilli and bell pepper from 5 different states of India, viz. Himachal Pradesh, Karnataka, Uttarakhand, Tamil Nadu and Haryana were characterized as translucent, yellow, raised colonies on YGCA medium, Gram negative, rod shaped, positive in starch hydrolysis, variation in pectin utilization. These isolates showed symptoms on chilli cv. Pusa Jwala and tomato cv. Pusa Ruby and they were grouped into pepper-tomato group (XCVPT), belonged to Xanthomonas euvesicatoria. Two sets of primers, i.e. Bs-XeF and Bs- XeR and Xeu 2.4 and Xeu 2.5 specific to X. euvesicatoria were used for further confirmation and the primers amplified DNA of all the isolates at 173bp and 208 bp respectively. Genetic diversity of 31 isolates of X. euvesicatoria along with four out group bacteria P. fluorescence DTPF-3, X. campestris pv. campestris Xcc-4, and Xcc-C23 and B. subtilis DTBS-5 was done by REP, ERIC and BOX- PCRs fingerprinting. Out of 12 DNA types, maximum isolates of X. euvesicatoria (12 isolates) belong to DNA type 2 isolated from tomato plants from different states of India and formed separated group isolated from pepper. High level of genetic diversity among the X. euvasicatoria isolates was observed. All out group bacteria were separated from X. euvesicatoria isolates.